1989
DOI: 10.1007/bf01247108
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants given repeatedly increase the behavioural effect of dopamine D-2 agonist

Abstract: The effects of single or repeated doses of antidepressant drugs (imipramine, amitriptyline, citalopram, mianserin) on rat locomotor hyperactivity induced by quinpirole, a dopamine D-2 receptor agonist, was investigated. Single doses of antidepressants do not change the effect of quinpirole, but enhance it when they are administered repeatedly. This enhancement is inhibited by (+/-)-sulpiride, a dopamine D-2 receptor antagonist. The results obtained indicate that the enhancement of dopaminergically-stimulated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…A similar increase in the effect of D-amphetamine and PRA, i.e. an enhanced response of dopamine D2 receptors, was observed after different antidepressants ), which we regarded as a result of increased affinity of those receptors for their agonists (Klimek and Maj, 1989;Maj, 1984Maj, , 1986Maj et al, 1989Maj et al, , 1996. Hence repeated PRA probably behaves likewise.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A similar increase in the effect of D-amphetamine and PRA, i.e. an enhanced response of dopamine D2 receptors, was observed after different antidepressants ), which we regarded as a result of increased affinity of those receptors for their agonists (Klimek and Maj, 1989;Maj, 1984Maj, , 1986Maj et al, 1989Maj et al, , 1996. Hence repeated PRA probably behaves likewise.…”
Section: Discussionsupporting
confidence: 60%
“…Besides, we administered PRA repeatedly and examined its effect on the locomotor hyperactivity induced by D-amphetamine or quinpirole. Our earlier findings showed that repeated administration of antidepressants with different pharmacological profiles enhanced the action of D-amphetamine, quinpirole and other dopamine stimulants (Maj, 1984(Maj, , 1986Maj et al, 1989). Similar effects were reported for a few antidepressants by other authors (Spyraki and Fibiger, 1981;Serra et al, 1979).…”
Section: Pramipexolesupporting
confidence: 67%
“…Repeated administrations of antidepressant drugs have been found to potentiate the locomotor stimulant effects of dopamine D 2 /D 3 agonists. These effects were apparent following systemic administration ; Maj and Wędzony 1988;Maj et al 1984Maj et al , 1989Martin-Iverson et al 1983;Płaźnik and Kostowski 1987;Willner and Montgomery 1981) or direct injection of D 2 /D 3 agonists into the nucleus accumbens Wędzony 1985,1988;Maj et al 1987). It is noteworthy that stereotypy, a behavioral effect induced by D-amphetamine and apomorphine, was not increased by repeated treatment of antidepressant drugs (Delini-Stula and Vassout 1979;Serra et al 1990;Spyraki and Fibiger 1981).…”
Section: Introductionmentioning
confidence: 90%
“…There is accumulating evidence suggesting that the administration of selective serotonin reuptake inhibitors (SSRIs), such as fluoxetine, citalopram, and paroxetine, alters the biochemical and behavioral responses to dopaminergic agents, as well as the basal activity of dopaminergic neurons. For example, the repeated administration of various SSRI appears to augment the behavioral response to dopamine (DA) receptor agonists such as quinpirole (Ainsworth et al, 1998;Collu et al, 1996Collu et al, , 1997Maj et al, 1989;Serra et al, 1992). A number of studies using various animal models of depression suggest that DA may play an important role in the antidepressant action of SSRI (Bonhomme and Esposito, 1998;D'Aquila et al, 1997;Renard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%